Downstream Effects of Industrial Effluents Discharge on Some Physicochemical Parameters and Water Quality Index of River Rido, Kaduna State, Nigeria - Ali Williams Butu; Chukwudi Nnaemeka Emeribe; Ijeoma Obianuju Muoka; Oluchi Favour Emeribe; Emmanuel Temiotan Ogbomida (Tecno Scientifica Publishing, 2022)
The effects of industrial effluent discharge on the water quality of River Rido in Kaduna South, Kaduna State, were examined. These include the Northern Noodles discharge point, the Kaduna Refinery discharge point, and points downstream of the River Rido. An interval of 100m between sampling points was established to achieve an even representation of sampling points. The physico-chemical parameters investigated include pH, free dissolved carbon dioxide, alkalinity, hardness, sodium, electrical conductivity, Turbidity, total suspended solids, total phosphate, nitrate, sulfate, and dissolved oxygen. Mean levels of turbidity Total suspended solids and total phosphate at effluent discharge points, as well as in most areas downstream of the study area, were generally above permissible limits for drinking water. Statistical differences were observed in the concentration levels of investigated parameters between the control point and effluent discharge points, as well as between the control point and areas downstream of the study area. However, concentration levels were observed to be similar between discharge points and areas downstream of the study area, an indication of contamination downstream by effluent discharge upstream. Notwithstanding, the water quality index of physico-chemical parameters at both effluent discharge points and areas downstream of River Rido shows that the quality of the river ranged from good to excellent at effluent discharge points and areas downstream of River Rido, respectively. This might be attributed to the effect of dilution from rainfall. It is therefore recommended that wastewater effluent from the refinery and northern noodles be properly treated before discharged into the study area.